ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK SEBELUM DAN SAAT PANDEMI COVID-19 DI INDONESIA PADA BANK PEMBANGUNAN DAERAH MENGGUNAKAN METODE CAMEL - Minadi Wijaya; Shifa Ummu Zhaba; Krisnhoe Sukma Danuta; Ginanjar Adi Nugraha (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to identify and analyze different levels of bank health in terms of each aspect of CAMEL at Regional Development Banks (BPD) before and during the Covid-19 Pandemic in Indonesia in 2018-2021. The research method used is a quantitative method. The data used is secondary data in the form of banking annual reports for 4 years of observation, from 2018 to 2021. The population of this study amounted to 27 banks, the entire population was sampled using the Total Sampling/Census technique. The analytical method used is descriptive statistical analysis and One- Way Anova test. The results show that there is no significant difference between BPD's Capital (CAR), Asset (NPL), Management (NPM), and Earning (ROA) between before and during the Covid- 19 Pandemic in Indonesia, while BPD Liquidity (LDR) has a significant difference between before and during the Covid-19 Pandemic in Indonesia. Efforts that need to be made by BPD are to increase the provision of capital adequacy, company profits and short-term liability capabilities so that the ratio value increases so that even in crisis conditions it can maintain the healthy of its bank in the healthy category or even increase, not decrease. Keywords: Bank Health; CAMEL Method; and Covid-19 Pandemic.